Using Brown Algae in the Plant–Soil System: A Sustainable Approach to Improving the Yield and Quality of Agricultural Crops - Oscar Sariñana-Aldaco; Luz Leticia Rivera-Solís; Adalberto Benavides-Mendoza; Armando Robledo-Olivo; Rosa María Rodríguez-Jasso; Susana González-Morales (Horticulturae)
The growing demand for food production and increasing stress scenarios increase the crucial need for sustainable alternatives to achieve increased crop yield and quality without affecting the environment. The use of brown macroalgae, being a renewable resource, is a promising option with various application options in agricultural systems, mainly in the form of extracts, direct applications, and compost. Brown algae are a source of active biomolecules and minerals that are currently used as agricultural biostimulants, since they increase crop productivity. This type of biostimulants derived from brown algae improve seed germination, increase the accumulation of plant biomass by accelerating cell division and elongation, activating the antioxidant system of plants, making them more resistant to stress, and contributes to the absorption and translocation of nutrients present in the soil. These products are also compatible with other agricultural inputs, such as synthetic fertilizers and pesticides, which makes them ideal for comprehensive applications and maintaining a balance in agroecosystems. This review incorporates fundamental and applied aspects of brown seaweeds that impact yields, biochemical quality, physiology, stress mitigation, and soil properties. Based on the above, the review is divided into different Sections that show the formulation of brown seaweed products; their effect on crop yield, quality, and physiology; their effect on biotic and abiotic stress mitigation; and their impact on soil physical, chemical, and biological properties.